Measuring consumer uncertainty about future inflation - Wandi Bruine de Bruin; Charles F. Manski; Giorgio Topa; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2009)
Survey measures of consumer inflation expectations have an important shortcoming in that, while providing useful summary measures of the distribution of point forecasts across individuals, they contain no direct information about an individual's uncertainty about future inflation. The latter is important not only for forecasting inflation and other macroeconomic outcomes, but also for assessing a central bank's credibility and effectiveness of communication. This paper explores the feasibility of eliciting individual consumers' subjective probability distributions of future inflation outcomes. In November 2007, we began administering web-based surveys to participants in RAND's American Life Panel. In addition to their point predictions, respondents were asked for their subjective assessments of the percentage chance that inflation will fall in each of several predetermined intervals. We find that our measures of individual forecast densities and uncertainty are internally consistent and reliable. Those who are more uncertain about year-ahead price inflation are also generally more uncertain about longer term price inflation and future wage changes. We find also that participants expressing higher uncertainty in their density forecasts make larger revisions to their point forecasts over time. Measures of central tendency derived from individual density forecasts are highly correlated with point forecasts, but they usually differ, often substantially, at the individual level. Finally, we relate our direct measure of aggregate consumer uncertainty to a more conventional approach that uses disagreement among individual forecasters, as seen in the dispersion of their point forecasts, as a proxy for forecast uncertainty. Although the two measures are positively correlated, our results suggest that disagreement and uncertainty are distinct concepts, both relevant to the analysis of inflation expectations.
Keywords: E52; D12; C81; 330; Inflation expectations; forecast uncertainty; wage expectations; probabilistic survey questions